Understanding Resilience in the Context of Sustainable HRM and the Human–Nature Relationship - Niemi, Sari; Pietiläinen, Ville; Suhonen, Marjo (Nordic Journal of Working Life Studies, 2025)
This study proposes that the deepening ecological crisis requires novel frameworks of resilience at work so that it considers the human–nature relationship. Increased sustainability reporting provides a platform to disclose how organizations practice sustainable HRM as a part of the SDGs. The research questions are: How are resilience approaches illustrated in sustainable HRM reporting? What argumentation is used for resilience approaches? What HRM practices are associated with different resilience approaches? The sustainability reports of 10 well-known Finnish organizations were studied using reflexive thematic analysis. The results identified that resilience is well addressed in the organizations’ SHRM at the individual and human interaction levels. However, the ecocrisis is not the challenge for which organizations are preparing SHRM in practice. Despite the good intentions of SHRM, the pursuit of resilience can lead to contradictions in terms of socioecological resilience. More conceptual guidelines are needed to emphasize the connection with the human–nature relationship.